MASCULINE DOMINATION IN DATING RELATIONSHIPS AMONG UNIVERSITY STUDENTS IN MAKASSAR CITY - Nizar Amalia Amanhy Damayanti; Rabina Yunus; Sakaria (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study explores the manifestations of masculine domination in dating relationships among university students in Makassar City, considering the interaction between global hegemonic masculinity concepts and the local socio-cultural context of Bugis-Makassar, which is rich with the value of siri' (honor). Using a descriptive qualitative approach, data were collected from students aged 18-24 through semi-structured in-depth interviews and non-participant observation, followed by thematic analysis. The findings reveal four main forms of masculine domination: (1) Control and surveillance through digital media, normalized as expressions of responsibility and protection; (2) Assertion of economic dominance and decision-making, with pressure on men to be breadwinners and final decision-makers; (3) Regulation of emotion and femininity expression, where men suppress "weak" emotions while controlling their partner's emotional expressions, and women self-censor their independence to avoid threatening masculinity; and (4) Normalization of psychological violence, rationalized as a form of "discipline" for the partner's good. The novelty of the study lies in its empirical contextualization of hegemonic masculinity and cyber dating abuse within the Bugis-Makassar cultural setting, revealing how global norms adapt and are reinforced by local cultural logics such as siri'. The research also highlights the internalization of patriarchal norms by both genders, which facilitates the normalization of control and psychological violence. Implications emphasize the need for contextually relevant relationship health education and dating violence prevention programs in universities, aiming to deconstruct narratives of "control as care" and "violence as discipline." Recommendations include multi-level interventions targeting peer group norms and broader societal discourses that support hegemonic masculinity.